Biogas production improvement and C/N control by natural clinoptilolite addition into anaerobic co-digestion of Phragmites australis, feces and kitchen waste. (March 2015) - Wang, Xiaowei; Zhang, Lieyu; Xi, Beidou; Sun, Wenjun; Xia, Xunfeng; Zhu, Chaowei; He, Xiaosong; Li, Mingxiao; Yang, Tianxue; Wang, Pengfei; Zhang, Zhonglei
Graphical abstract: Highlights: Better biogas production was found by clinoptilolite than bentonite and diatomite. Clinoptilolite addition shortened the lag phase of anaerobic co-digestion. Clinoptilolite enhanced organic carbon matters destruction. Clinoptilolite can optimally control the ratio of C/N in anaerobic co-digestion. Abstract: Anaerobic co-digestion (A co-D) performance of Phragmites australis, feces and kitchen waste with addition of clinoptilolite (one main kind of zeolite) was investigated to evaluate the improvement of biogas/methane production and internal mechanism of nitrogen and organics control. A better biogas/methane production was observed by 10% clinoptilolite (v/v) than bentonite and diatomite, with the shortest lag phase of 0.070 d −1, the max rate of 15.89 L/(kg VS day) and ultimate biogas production of 308.2 L/kg VS as the modified Gompertz equation predicted. Accordingly, the content of methane in the biogas was increased from 44.10% to 65.30%. Furthermore, the clinoptilolite inhibited the acidification of digestion liquid (optimum pH 7.0–7.5) and enhanced the VFAs (acetic acid, propionic acid and butyric acid) destruction. Moreover, 10% of clinoptilolite optimally enhanced the microbial utilization of Ca 2+ /Mg 2+, controlled the C/N ratio, and improved the biogas production as well as NH3 -N/NO3 -N inhibition efficiency.